Crossmodal correspondences and attention in the context of multisensory (product) packaging design - Velasco, C (2015)
The term 'crossmodal correspondence' refers to the tendency for people to match information across the senses. In this thesis, the associations between taste/flavour (tastants and words) information with shapes and colours is investigated. Furthermore, such correspondences are addressed in the context of multisensory packaging design. The focus in this thesis is on the way in which taste/flavour information can be communicated by means of the visual elements of product packaging. Through a series of experiments, I demonstrate that people associate tastes and the roundness/angularity of shapes, and that taste quality, hedonics, and intensity influence such correspondences. However, packaging roundness/angularity does not seem to drive these associations. Additionally, I demonstrate that culture and context systematically influence colour/flavour associations. Importantly, the results reported in this thesis suggest that taste/shape correspondences can influence taste expectations as a function of the visual attributes of product packaging. The results reported here also reveal that colour can influence the classification of, and search for, flavour information on a product’s packaging. It turns out that the strength of the association between a flavour category and a colour is crucial to such an effect. The implications of these findings are discussed in light of the theories of crossmodal correspondences, its applications, and directions for future research.